2007
DOI: 10.1038/sj.jes.7500623
|View full text |Cite
|
Sign up to set email alerts
|

Panel discussion review: session two — interpretation of observed associations between multiple ambient air pollutants and health effects in epidemiologic analyses

Abstract: Air pollution epidemiologic research has often utilized ambient air concentrations measured from centrally located monitors as a surrogate measure of exposure to these pollutants. Associations between these ambient concentrations and health outcomes such as lung function, hospital admissions, and mortality have been examined in short-and long-term cohort studies as well as in time-series and case-crossover studies. The issues related to interpreting the observed associations of ambient air pollutants with heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In our previous study on air pollution and birth weight we found consistently stronger associations for BTEX than for NO 2 , but in the present study none clearly emerged as a potentially better marker of altered fetal growth due to exposure to traffic-related air pollution (although results from the previous and the present study cannot be interpreted as fully independent). Overall, the high correlation in space and time between pollutants sharing similar sources, together with the lack of enough knowledge on underlying casual pathways, makes it difficult to separate the etiologic agents and to disentangle the role of independent pollutants in causing adverse health effects (Kim et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In our previous study on air pollution and birth weight we found consistently stronger associations for BTEX than for NO 2 , but in the present study none clearly emerged as a potentially better marker of altered fetal growth due to exposure to traffic-related air pollution (although results from the previous and the present study cannot be interpreted as fully independent). Overall, the high correlation in space and time between pollutants sharing similar sources, together with the lack of enough knowledge on underlying casual pathways, makes it difficult to separate the etiologic agents and to disentangle the role of independent pollutants in causing adverse health effects (Kim et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…As many of these issues are shared across all pollutants, they will not be discussed in detail here. These issues include statistical model choice (HEI, 2003;Erbas & Hyndman, 2005;Ito, Thurston & Silverman, 2007) and the challenges of distinguishing the effects of different pollutants in multipollutant models (Kim et al, 2007;Billionnet, Sherrill & Annesi-Maesano, 2012). The low average concentrations of SO 2 , but with sharp peaks, combined with the fact that, in some studies, SO 2 is controlled for PM 10 that is measured only once every 6 days means that the presence of measurement error adds uncertainty to the interpretation of the multipollutant model results.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the field has seen growth in the number of methodological approaches used to estimate the joint health effects of multiple air pollutants [7, 8]. A recent review of studies that implemented multipollutant exposure metrics to estimate health effects of ambient air pollution reported that although multipollutant exposure metrics were limited by the lack of ‘gold standard’, these approaches have been useful for characterizing multipollutant exposures [9].…”
Section: Introductionmentioning
confidence: 99%